Exacerbation of innate immune response in mouse primary cultured sertoli cells caused by nanoparticulate TiO2 involves the TAM/TLR3 signal pathway. Issue 1 (27th September 2016) - Wu, Nan; Hong, Fashui; Zhou, Yingjun; Wang, Yajing
Abstract: Sertoli cells provide appropriate mitogens, differentiation factors and sources of energy for developing germ cells throughout the lifetime of males, and protect these germ cells from harmful agents and from the host's own immune system. Therefore, reductions in the rate and quality of spermatogenesis caused by nanoparticulate titanium dioxide (nano‐TiO2 ) may be closely involved in the immunoregulation of Sertoli cells. However, the underlying mechanism of this response is still unclear. To address this issue, we used mouse primary cultured Sertoli cells to examine the toxic effects of nano‐TiO2 via alterations in morphology, cell viability, and activation of the TAM/TLR3 signal pathway. The results demonstrated that nano‐TiO2 could cross the cytomembrane into the cytoplasm or nucleus, decrease Sertoli cell viability, damage morphology (such as elongated fusiform, cellular and nuclear shrinkage) and induce the expression of various immune mediators and inflammatory cytokines, including TLR3(+0.31‐fold to +0.81‐fold), IL‐lβ(+0.33‐fold to +5.0‐fold), NF‐κB(+0.22‐fold to +3.65‐fold), IL‐6(+0.47‐fold to +3.53‐fold), TNF‐α(+0.14‐fold to +2.44‐fold), IFN‐α(+0.17‐fold to +2.27‐fold), and IFN‐β(+0.09‐fold to +2.29‐fold), and suppress the expression of Tyro3(−9.33% to −61.93%), Axl(−19.03% to −60.67%), Mer(−8.04% to −59.16%), and IκB(−34.35% to −86.59%) in primary cultured Sertoli cells. These results suggest that testicular innate immune responses to pathogens caused by nano‐TiO2 may be involved in the regulatory mechanisms of TAM/TLR3 signaling in testicular Sertoli cells. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 198–208, 2017.